Pañjāba dā itihāsa, 1849-1947 - Sudarashana Siṅgha. (Paṭiālā : Pabalīkeshana Biūro, Pañjābī Yūnīwarasiṭī, 1991)
History of Punjab, 1849-1947.
In Panjabi.
Includes bibliographical references (p. [145]-147).
Mode of access: Internet.
Keywords: Punjab (India) -- History